c.2 - Shariff, Abusaleh (Delhi, 1999)
The HDR is the outcome of a nationally representative survey covering different facets of human development. Based on a primary survey of 33,000 households located in 15 major Indian states and the north-eastern region, the report covers aspects such as the level of living, employment and wages, literacy and education, morbidity, disability and nutrition, effectiveness of public services like PDS, education and health and demographic characteristics.
Keywords: States India profile